The immunopathogenesis and treatment of tuberculous pericardial effusions in a population with a high prevalence of infection with the human immunodeficiency virus - Reuter, Helmuth (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DMed (Medicine. Internal Medicine))-University of Stellenbosch, 2005.